Current Developments in Monetary and Financial Law, Volume 6 : Restoring Financial Stability--The Legal Response. (International Monetary Fund, 2013)
'Restoring Financial Stability-The Legal Response' is the theme of the sixth volume of 'Current Developments in Monetary and Financial Law.' The book covers a range of issues: frameworks and regulatory reforms in the United States, European Union, and Japan that address systemic risk; the international dimension of financial stability; the regulation of complex financial products; cross-border banking supervision; capital adequacy; and corporate and household debt restructuring. The chapters are based on presentations from a seminar hosted by the IMF Legal Department, the Ministry of Finance of Japan, the Financial Services Agency of Japan, and the Bank of Japan, with the assistance of the IMF Institute. The contributors to the volume come from both the public and private sectors, and include academics, lawyers practicing in the fields of banking and financial law, and officials from central banks, supervisory and regulatory agencies, and standard-setting bodies.